1992
DOI: 10.1203/00006450-199208000-00009
|View full text |Cite
|
Sign up to set email alerts
|

A Mutation in the E1α Subunit of Pyruvate Dehydrogenase Associated with Variable Expression of Pyruvate Dehydrogenase Complex Deficiency

Abstract: ABSTRACT. Defects in pyruvate dehydrogenase, the first catalytic component of the pyruvate dehydrogenase complex, are the most common cause of pyruvate dehydrogenase complex deficiency. A family with variable pyruvate dehydrogenase complex deficiency had been described in which cultured skin fibroblast s of affected family members had normal pyruvate dehydrogenase complex activity, but different tissues and blood lymphocytes had significantly diminished activities. Enzymatic activity and immunoblot studies ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 24 publications
3
13
0
Order By: Relevance
“…Two of the eight mutations found in our patients (R263G and R302C) have already been described previously (Wexler et al, 1992;Chun et al, 1'993;Dahl et al, 1992b;De Meirleir et al, 1993). The clinical history of female patient 2 (R30;!C mutation) is very similar to already described patients carrying this mutation.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Two of the eight mutations found in our patients (R263G and R302C) have already been described previously (Wexler et al, 1992;Chun et al, 1'993;Dahl et al, 1992b;De Meirleir et al, 1993). The clinical history of female patient 2 (R30;!C mutation) is very similar to already described patients carrying this mutation.…”
Section: Discussionsupporting
confidence: 78%
“…Cultured skin fibroblasts are most frequently used for diagnosis. As previously mentioned, most of the mutations in PDH complex deficiencies are found in the E l a m b u n i t of the complex; however, the expression of this gene at the mRNA level does not appear to be altered in most of the patients (Dahl et al, 1992a,b;Dahl and Brown, 1994;De Meirleir et al, 1992Chun et al, 1993;Wexler et al, 1992;Matthews et al, 1993;Hansen et al, 1993;Takakubo et al, 1993a,b;Endo et al, 1989Endo et al, , 1941. We describe the detection of mutations in the E,a gene of eight patients with a PDH complex deficiency.…”
Section: Introductionmentioning
confidence: 85%
“…Four mutations lie within this region in five unrelated patients. Indeed, the mutation R263G has been identified in five families, making it the most common PDH mutation to date (Chun et al 1993(Chun et al , 1995Wexler et al 1992;Lissens et al 1996; Table 2). The clinical histories of these patients are similar, except for our case 1 who died earlier than the other R263G cases.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of PDH deficiency depends on the measurement of residual enzyme activity in fresh lymphocytes, lymphoblastoid cell lines, cultured skin fibroblasts or muscle tissue. At least 70 patients with PDH deficiency have been reported so far and 52 different mutations in the coding region of the Ε1α subunit have been described (Kerr et al 1988Endo et al 1989Endo et al , 1991Dahl et al 1990Dahl et al , 1992Chun et al 1991Chun et al , 1993Chun et al , 1995Hansen et al 1991Hansen et al , 1993Hansen et al , 1994De Meirleir et al 1992Ito et al 1992Ito et al , 1995Wexler et al 1992Wexler et al , 1995Matthews et al 1993Matthews et al a, b, 1994Takakubo et al 1993Takakubo et al a, b, 1995Awata et al 1994;Dahl and Brown 1994;Fujii et al 1994;Naito et al 1994a, b;Hemalatha et al 1995;Lissens et al 1995Lissens et al , 1996Matsuda et al 1995;Tripatara et al 1996). Two mutations in E3 have also been identified (Liu et al 1993) but, so far, no molecular mutations have been reported that specifically affect the E1β subunit, E2, component X or PDH-phosphatase.…”
Section: Introductionmentioning
confidence: 97%
“…There are several reports of E l a deficiency associated with a decreased Elf3 immunoreactivity [5,12,24,[26][27][28]. These authors speculated that a mutation affecting the expression of one of the subunit proteins causes the remaining uncomplexed subunit to be unstable.…”
Section: Discussionmentioning
confidence: 96%